PERAN GURU PENDIDIKAN AGAMA KATOLIK DALAM MEMERANGI RADIKALISME DI SMP SWASTA SANTO XAVERIUS 2 KABANJAHE - Johannes Sohirimon Lumban Batu; Din Oloan Sihotang (Bahasa Indonesia, 2022)
This study aims to describe the role of Catholic religious education teachers in countering religious radicalism at Private Junior High School Santo Xaverius 2 Kabanjahe. The research method used is a descriptive qualitative approach. The data of this study were sourced from the results of interviews and observations. The subjects in this study were 2 teachers of Catholicism and 60 students from grades VII, VIII and IX. The interview data that was explored was how the strategies used by the teacher were to shape the character of good students in order to avoid radical understanding. Observation data comes from activities carried out by teachers of Catholic education subjects during the learning process in class. The data were then analyzed using the data reduction stage, data presentation and conclusion drawing. The results of the study found that the role of Catholic religious teachers to shape students' character as a strategy against religious radicalism were: a) teaching religious education in schools, b) cooperating with parents or guardians of students in educating religious materials in the family, and c) cooperating with deacon of the Church.